1982
DOI: 10.1271/bbb1961.46.1403
|View full text |Cite
|
Sign up to set email alerts
|

Participation of amino groups in lipolytic action of growth hormone.

Abstract: Wepreviously reported that a fragment, A-II, isolated from a tryptic digest of bGHretained significant amounts of growth-promoting activity in rats and in vitro metabolism-stimulating activity in adipose tissue of hypophysectomized rats.1)2) It has also been demonstrated that A-II shows metabolic activities in humans similar to hGH.3>4) Since A-II is a peptide originating from the 96-133 portion ofbGH and has a structure similar to those of 96-133 ofoGH and 95-133 ofhGH and hCS, it has been suggested that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
1988
1988

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In this study, we showed that replacement of Arg-Glu by Lys-Asp led to a decrease in potency of the lipolytic action and that blocking the free guanidino group of Arg with nitro group resulted in loss of FF A release (Table II). Yamasaki et al 7 ) reported that blocking the free amino group of bovine growth hormone with an acetyl group caused a marked decrease in potency of its lipolytic action. These results suggest that a free guanidino or amino group may be important for a lipolytic action on fat cells.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we showed that replacement of Arg-Glu by Lys-Asp led to a decrease in potency of the lipolytic action and that blocking the free guanidino group of Arg with nitro group resulted in loss of FF A release (Table II). Yamasaki et al 7 ) reported that blocking the free amino group of bovine growth hormone with an acetyl group caused a marked decrease in potency of its lipolytic action. These results suggest that a free guanidino or amino group may be important for a lipolytic action on fat cells.…”
Section: Discussionmentioning
confidence: 99%